(3TQM CQLhRI GHf SjfG aj GdWHs - (3CHh GdMLGL , jhSa Hf eMeO WedhS , GdMcjes; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3YHO QHg eMeO Hf eMeO Hf YdGd GdTQjai s)
(3ChdgG (B:s
(3GdMeO Ydi SHhZ EMSGfg aEfi deG QCjJ eQGJH GdYde CTQa GdeQGJH , LYdJ JCdjai dgPG GdcJGH hSjdI HQjOi def cKQ EMSGfg Edi haVdg Ydi GdTjN GdCLd CHh jMji Hf s
(3BNQgG (B:s
(3hEeG bdJ eG bGdhg , hdYd efg HYV GdeSGFd Ch CcKQ ef GdeSGFd hbO Bf Cf CbWY bhdi dGSJjaGA eG bUOJg s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B126 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B265 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs